Study of Variability in Long-term Multiwavelength Optical Lightcurves of Blazar AO 0235+164 - Cellone, Sergio Aldo (2023)
We present a long-term and intraday variability study of optical multiwaveband (UBVRI) data from the blazar AO 0235+164 collected by various telescopes for ∼44 yr (1975–2019). The blazar was found to be significantly variable over the years in all wave bands with a variation of about 6 mag between its low and active states. The variations in the different wave bands are highly correlated without any time lag. We did not observe any significant trend in color variation with time, but we observed a bluer-when-brighter trend between the B − I color index and the R magnitude. Optical BVR-band spectral energy distributions always show a convex shape. Significant intraday variability was frequently seen in the quasi-simultaneous observations of AO 0235+164 made on 22 nights in the R and V bands by the CASLEO and CAHA telescopes during 1999–2019. We also estimated a central supermassive black hole mass of 7.9 × 10⁷ M☉ by analyzing the broad Mg II emission line in AO 0235 +164ʼs spectrum. We briefly explore the probable physical scenarios responsible for the observed variability.